2003
DOI: 10.1063/1.1597944
|View full text |Cite
|
Sign up to set email alerts
|

Proton implantation effects on electrical and recombination properties of undoped ZnO

Abstract: Electrical and optical properties of undoped n-ZnO crystals implanted with 50 keV protons with doses from 5×1013 to 5×1015 cm−2 are reported. Proton implantation leads to a decrease of the carrier concentration in the near-surface region, but at the end of the proton range shallow donors are observed whose concentration tracks the implant dose and that we attribute to hydrogen donors. Three deep electron traps with apparent activation energies of 0.55, 0.75, and 0.9 eV are introduced by proton implantation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 16 publications
4
38
0
Order By: Relevance
“…There have also been a number of reports on laser emission from ZnO-based structures at room temperature (RT) and beyond. Several experiments confirmed that ZnO is very resistive to high energy radiation [9][10][11] making it a very suitable candidate for space applications. ZnO is easily etched in all acids and alkalis, and this provides an opportunity for fabrication of devices with considerable ease.…”
Section: Introductionmentioning
confidence: 75%
“…There have also been a number of reports on laser emission from ZnO-based structures at room temperature (RT) and beyond. Several experiments confirmed that ZnO is very resistive to high energy radiation [9][10][11] making it a very suitable candidate for space applications. ZnO is easily etched in all acids and alkalis, and this provides an opportunity for fabrication of devices with considerable ease.…”
Section: Introductionmentioning
confidence: 75%
“…The 0.9-eV hole trap was reported in vapor transport grown bulk ZnO, for both a virgin sample and a sample implanted with 100-keV protons. 18 In Ref. 18, the authors invoked an early review that related these centers to oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…18 In Ref. 18, the authors invoked an early review that related these centers to oxygen vacancies. In contrast to the behavior of the other traps, the DLTS signal of H5 shows an anomalous increase as the measurement period T W increases ͑or the "rate window" decreases͒, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Through first principles total energy calculations, we show that the transition between α-and β-type configurations results in metastable behavior of these defects. Specifically, we predict that the oxygen vacancy V O leads to persistent electron photoconductivity (n-type PPC) in n-ZnO observed recently after proton irradiation [18], whereas the Se vacancy V Se causes persistent hole photoconductivity (p-type PPC) in p-CuInSe 2 or p-CuGaSe 2 , constituting the unusual case where a donor-like defect causes p-type PPC. Thus, our results shed new light on hitherto unknown physical origin of the phenomenon of light-induced metastability in chalcopyrite CuInSe 2 based photovoltaic devices exhibiting p-type PPC [19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%